Biomechanical responses of temporomandibular joints during the lateral protrusions: A 3D finite element study. (October 2020) - Shu, Jingheng; Teng, Haidong; Shao, Bingmei; Zheng, Tinghui; Liu, Yang; Liu, Zhan
Highlights: 3D dynamic finite element analysis of lateral protrusions was carried out. A more relaxed position was used to decrease the initial stress status. The squeeze and the stretch by the attachment were two reasons to increase the stress on the disc. Abstract: Background & objective: This study aims to analyze the stress distributions in temporomandibular joints (TMJs) during the left and right protrusions and explore the mechanical reasons for these stress distributions. Methods: Computed tomography and magnet resonance images of 5 asymptomatic subjects were used to reconstruct the bone and soft tissue of the maxillofacial models with a pair of detailed TMJs. An optical motion-track system captured the left and right protrusions of the subjects. Inhomogeneous material properties were assigned to the models according to the gray value of the images. Then, the captured data were inputted as the loadings of the finite element models. Different from previous studies, a more relaxed position was used as the initial position of the jaw, which could better mimic the internal loads with lower initial stress. Results: The stresses on the discs for all the subjects during the motions were under the fracture stress. The stress distributions exhibited an obvious asymmetry. Among them, three subjects had a contralateral-greater stress distribution during both left and right lateral protrusions. The greater stresses always lay in the left disc for one subject, and another subject had an ipsilateral-greater stress distribution during the motions. Besides, the stress distributions in a single disc were various due to the different nature of movements. Conclusion: Excessive stretch and squeeze, which was originated from great and little condylar displacements towards fossa during the motions, had a negative influence on the stresses in discs. Thus, the detections about the condylar displacement, even biomechanical analysis, were necessary to provide dynamically biomechanical information in the treatment of TMJ associated dysfunctions.